Self-Control in Adolescents with Online Gambling Addiction - Pasha Dwi Novita; Nurul Huda Nabillah; Sarah Kemala Oktaviani; Bunga Aisya; Agitia Kurniati Asrila (CAUSALITA : Journal of Psychology, 2026)
The phenomenon of online gambling addiction among adolescents is increasing with the ease of internet access and digital platforms. This study aims to analyze self-control in adolescents experiencing online gambling addiction based on five dimensions of self-control according to Averill (1973). The research method uses a qualitative approach with in-depth interview techniques on two adolescent subjects experiencing online gambling addiction. Data were analyzed using thematic analysis based on five dimensions of self-control: behavioral control, cognitive control, decisional control, information control, and retrospective control. The results showed that both subjects experienced self-control disorders in various dimensions, with different patterns between the first and second subjects. The first subject showed weaker behavioral control but better cognitive awareness, while the second subject showed very low decisional control but better information control. The conclusion of this study shows that online gambling addiction in adolescents is closely related to low self-control in various dimensions, which requires appropriate psychological intervention to help adolescents overcome addiction.